What is a capable guardian to older fraud victims? Comparison of younger and older victims’ characteristics of online fraud utilizing routine activity theory - Parti, Katalin (Frontiers in Psychology, 2023)
The paper maps which sociodemographic and situational characteristics make people vulnerable to manipulative online fraud (scams), comparing older and younger individuals’ risk and protective factors. On a large national sample of US adults we find that time spent on a computer, familiarity with computers, and applying antivirus software and firewall determine online victimization in older individuals, similarly to younger age groups. However, older victims differ in characteristics from younger victims. They are less likely to apply very simple tools such as camera cover, identity theft monitoring, and credit card freeze, even after experiencing online scams. In addition, having a full-time job and being financially active make older individuals more prone to answer cold calls and phishing emails than retired individuals. Single parenthood or being the primary caretaker of a young child is protective for older individuals. However, older victims are less likely to report scams than younger ones. We propose that relatives and family members should also be included in awareness programs to help older victims overcome the financial and emotional loss an online fraud brings about. Furthermore, employers should address the unique vulnerabilities of older individuals in comprehensive fraud prevention programs. Besides pure technical protection, programs must cover social manipulation techniques as fraud prevention.